Synthesis and Antibacterial Activity of Grafted Poly(Vinyl Chloride) Polymer against Gram-Positive and Gram-Negative Bacteria - Shrajan Kotian; Sonali Gupta; Yashoda Malgar Puttaiahgowda; Sanmit Shetty (Advances in Polymer Technology)
Infectious diseases caused by microorganisms have gained worldwide attention in recent years. According to data compiled by the World Health Organization, the number of deaths resulting from infectious diseases is on the rise. In light of these dangers, the study of antibacterial materials has become increasingly vital. In this research, an antibacterial polymer was developed using poly(vinyl chloride) (PVC) and 4,4-diamminodiphenylmethane (DDM). The produced polymer’s chemical structure and thermal properties were investigated using Fourier-transform infrared spectroscopy, nuclear magnetic resonance, and thermo-gravimetric analysis. The antibacterial activity of the resulting PVC-g-DDM polymer was effective in killing both Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli. The antimicrobial efficacy was tested using a spread plate method, demonstrating its potential utility in a variety of applications like biomedical, coatings, water purification systems, and others. Antimicrobial resistance is increasing, especially among bacteria that have acquired resistance to multiple therapeutics. To fully optimize and explore the polymer’s potential and its usage, more research is needed.